Exploring the Tazkir al-Ghabi Manuscript: The Sufistic Pattern of Sheikh Burhanuddin in the Minangkabau - Erman, Erman; Komaruddin, Komaruddin; Darusalam, Darusalam (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2024)
This article explores the Sufistic thought of Sheikh Burhanuddin as presented in his work, “Tazkir al-Gabi”. This work is significant for its potential to elucidate the history of Sufism’s development in the Minangkabau and Malay Islamic world. This study employs a qualitative method with a historical approach, incorporating heuristics, source criticism, interpretation and historiography to uncover the history of “Tazkir al-Gabi” and Sheikh Burhanuddin’s Sufistic thought. The findings reveal that “Tazkir al-Gabi” is a critical work directly linked to 14th-century Sufism historical sources. It presents a Sunni Sufism interpretation style, particularly in discussions about divinity and Sufism. “Tazkir al-Gabi” also embodies efforts to reconcile Sufism and Shari’a, specifically in clarifying the understanding of wujudiyah in Syattariyah teachings in Minangkabau. This reconciliation is evident in the interpretation of physical and spiritual deeds, underscoring the importance of Sharia-based deeds in Sufism. The study’s implications highlight the need for optimal exploration of local manuscripts to understand the diversity of religious discussions within their cultural contexts.